2010
DOI: 10.1103/physreva.81.022904
|View full text |Cite
|
Sign up to set email alerts
|

X-ray mass attenuation coefficients and imaginary components of the atomic form factor of zinc over the energy range of 7.2–15.2 keV

Abstract: X-ray mass attenuation coefficients and imaginary components of the atomic form factor of zinc over the energy range of 7.2-15.2 keVThe x-ray mass attenuation coefficients of zinc are measured in a high-accuracy experiment between 7.2 and 15.2 keV with an absolute accuracy of 0.044% and 0.197%. This is the most accurate determination of any attenuation coefficient on a bending-magnet beamline and reduces the absolute uncertainty by a factor of 3 compared to earlier work by advances in integrated column density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 71 publications
3
28
0
Order By: Relevance
“…Unlike the Si data, this set shows closer agreement to the XCOM predictions, though the data dip towards the FFAST predictions just above the Al Kα x-ray energy. This effect is similar to a trend observed below the K edge for four previously mentioned experiments: Ag [23], Mo [24], Cu [25] and Zn [26]. In each case, the data in this energy region agree with XCOM but drop to midway between the two theories, into slightly closer agreement with FFAST, in the vicinity of the Kα energy.…”
Section: Comparison Of Light Element Experimental Work With Theorysupporting
confidence: 89%
See 2 more Smart Citations
“…Unlike the Si data, this set shows closer agreement to the XCOM predictions, though the data dip towards the FFAST predictions just above the Al Kα x-ray energy. This effect is similar to a trend observed below the K edge for four previously mentioned experiments: Ag [23], Mo [24], Cu [25] and Zn [26]. In each case, the data in this energy region agree with XCOM but drop to midway between the two theories, into slightly closer agreement with FFAST, in the vicinity of the Kα energy.…”
Section: Comparison Of Light Element Experimental Work With Theorysupporting
confidence: 89%
“…A recent and extensive set of synchrotron radiation measurements has appeared [20][21][22][23][24][25][26][27][28] in which the authors demonstrated painstaking effort to eliminate systematic errors identified in earlier measurements [15][16][17]. They examined attenuation coefficients for elements Si, Cu, Zn, Ag, Mo, Sn and Au with generally an overall five-fold improvement in measurement accuracy (typically to within 0.1-0.2%) with respect to earlier work.…”
Section: Previous Experimental Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The simple picture is modified by possible effects of beam harmonic contamination and of dark current drift of the detectors with the contribution ε ( E ) to the transmitted beam: A i ( E ) = −ln[ ε ( E ) + exp(− μ ( E ) d i )]. Now, the ratios R are not constant: any variation in the ratio, especially any residual of the edge or XAFS features, indicates a contamination.…”
Section: Discussionmentioning
confidence: 99%
“…The compilations claim a 1% accuracy in the »smooth« energy regions far from absorption edges and 4%–20% in the vicinity of the absorption edges even in monatomic gases free of XAFS modifications of the absorption. Direct measurements have since only been performed on a few selected elements for the purpose of recalibration of compiled data or in conjunction with inner‐shell atomic spectroscopy . It has been realized that with the advance of X‐ray sources and detectors, the accuracy of the absorption coefficient depends mostly on the definition of the sample rather than on the spectroscopic measurement itself.…”
Section: Introductionmentioning
confidence: 99%